تطوير منصة إتقان العالمية للمؤسسات القرآنية والتعليمية (مبادرة ماليزية عُمانية = Developing ITQAN Platform for Quranic education institutions Malaysian-Omani Initiative - Abdo Khaled, Nashwan; Alzahimi, Saleh; Assad, Mohammed Abdulhakim; Zaid, Mohammed; Anoah, Salah (2019)
Nowadays, the use of IT is playing a crucial rule in almost all aspects of life. This paper will highlight the importance of using IT in education. With that, it is observed that many software and programs are competing in the world, but there is still a lack in integrating Quranic models in educational ERP systems. ITQAN Platform for Educational Institutions has been proposed and developed to realise this objective for the whole processes of Quranic education along with other education models within the institution. The system encompasses 10 main modules – admission, curriculum, activities, branches, Quranic modules, finance, forms, planning, human resources and website management. Within each and every module there are submodules. The system has been tested within ITQAN institution and proved to be useful for other schools and educational institutions.